2007
DOI: 10.1517/14656566.8.3.279
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk in women: the impact of hormone replacement therapy and prospects for new therapeutic approaches

Abstract: Cardiovascular disease (CVD) is the main cause of death in women. Observational studies of hormone replacement therapy (HT) and data from women with premature ovarian failure have provided support for the principle that estrogen confers protection against the development of CVD in premenopausal women. However, randomised, controlled trials investigating HT in postmenopausal women have failed to demonstrate a benefit of HT in the primary or secondary prevention of CVD. Nevertheless, HT may be effective if targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 80 publications
0
9
0
3
Order By: Relevance
“…Accordingly, estrogen, its receptor and its coregulatory proteins, has been implicated in the pathologies of a variety of diseases and cancers [13, 14, 15, 16]. Furthermore, these large pleiotropic effects are a serious complication in using hormone or hormone derivatives as potential therapeutics [17, 18, 19]. Technologies that increase specificity for estrogen activity or possibly target it to cells, tissues or independent genes, have tremendous applicability in therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, estrogen, its receptor and its coregulatory proteins, has been implicated in the pathologies of a variety of diseases and cancers [13, 14, 15, 16]. Furthermore, these large pleiotropic effects are a serious complication in using hormone or hormone derivatives as potential therapeutics [17, 18, 19]. Technologies that increase specificity for estrogen activity or possibly target it to cells, tissues or independent genes, have tremendous applicability in therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…Although apoM is not present in all HDL particles, recent data have demonstrated a positive correlation between serum apoM levels and HDL cholesterol concentrations in man [9]. Wolfrum and his 4 colleagues, using apoM-deficient mice, demonstrated that apoM is important for preβ-HDL formation and cholesterol efflux from macrophages; thus, apoM-deficient HDL was markedly less efficient in facilitating cholesterol efflux from macrophages in vitro than normal HDL [10]. Moreover, over-expression of apoM in LDL-receptor knock-out mice protected against atherosclerosis when fed a high cholesterol diet [10], suggesting that apoM may play an important role in HDL metabolism and protect against atherosclerosis.…”
mentioning
confidence: 98%
“…In general, these effects of estrogen are considered beneficial from the atherogenic point of view. However, randomised, controlled trials of estrogen supplementation in postmenopausal women have failed to demonstrate a benefit of estrogens in the primary or secondary prevention of cardiovascular diseases (CVD), although estrogens might be effective if targeted at younger perimenopausal women [4].…”
mentioning
confidence: 99%
“…It is related to the symptoms and metabolic effects of sex steroid deficiency, as well as the emotional sequelae experienced by couples who have difficulty in conceiving a pregnancy [34]. In addition, POF is associated with risks of cardiovascular disease, osteoporosis, and psychiatric diseases [3537]. Currently, there are no effective treatments for this disease.…”
Section: Discussionmentioning
confidence: 99%